Digital Entrepreneurship Readiness and Challenges Faced by Women-Owned SMEs in Maros Regency - Mutiara, Tresna; Merdiwijayan, Bagus (Generasi Sains Indonesia, 2025)
The rapid growth of digital technologies has created new opportunities for small and medium enterprises (SMEs) to expand their markets and improve operational efficiency. This study focuses on the digital entrepreneurship readiness and challenges faced by women-owned SMEs in Maros Regency, South Sulawesi, Indonesia. The study employed a quantitative research design, using a survey with 120 women SME owners to assess their digital literacy, access to technology, financial readiness, and perceived barriers to digital adoption. The results indicate that while 62% of respondents exhibit moderate digital readiness, only 38% have fully integrated digital tools such as e-commerce platforms, online marketing, and digital payments into their businesses. The main challenges identified include limited digital skills, financial constraints, poor internet access, and gender-related constraints. Despite these challenges, many women entrepreneurs recognize the potential of digital tools to enhance their income and independence. The findings suggest that training programs, affordable digital infrastructure, and financial inclusion initiatives are essential to empower women entrepreneurs in the digital era. This study contributes to understanding how gender-specific barriers impact digital adoption in rural and semi-urban contexts and offers recommendations for policy interventions. Future research could focus on evaluating the long-term effects of digital empowerment programs on women-owned SMEs.